Produção de ácido lático a partir da conversão hidrotérmica do glicerol via catálise homogênea e heterogênea - Rodrigues, Anne Kerolaine de Oliveira (2016)
The use of alternative energy sources is a of the major current priorities, that appears to circumvent the serious problems caused by technological development. Accordingly, biodiesel arises as an alternative fuel to petroleum. However, high biodiesel production generates a large quantity of glycerin (10 wt%) which is considered an unwanted byproduct. To increase the market values of the biodiesel byproduct, it is necessary to convert glycerin into other chemicals, such as in lactic acid, which is becoming increasingly important due to their promising polymers applications - eg.: poly(lactic acid) (PLA) - as an alternative to replace petrochemical plastics. In the present study the hydrothermal process was used for lactic acid production, replacing the fermentation process that is currently used to obtain this product. For hydrothermal conversion of glycerol into lactic acid by homogeneous catalysis, NaOH and KOH catalysts were used. And for hydrothermal glycerol lactic acid by heterogeneous catalysis, Cu/SiO2 catalyst was used. Initial glycerol concentration (0.51-17.1 M), temperature (160-280 °C), pressure (2-43 bar), water/glycerol volumetric ratio (0.8 to 31), catalyst/glycerol molar ratio (0.01 to 1.02) and total reaction time (3-4 hours) were the variables studied with temperature and water/glycerol volumetric ratio having the major influence. In addition, a first-order kinetic model for glycerol concentration versus time was developed and verified experimentally under conditions with different temperatures. Comparing the results obtained from hydrothermal conversion by homogeneous and heterogeneous catalysis, it was observed that KOH was catalyst with the best performance. The highest yield obtained was 87.5% at 220 °C and 28.8 bar, after 3 h, from a solution water/glycerol volumetric ratio equal to 0.8 and KOH/glycerol molar ratio equal to 0.03. From this result, hydrothermal process can be seen as a promising method to add value to glycerol.